Case Report: Off Label Utilization of Topiramate and Metformin in Patients With BMI ≥50 kg/m2 Prior to Bariatric Surgery - Sari, Cetin; Seip, Richard L.; Umashanker, Devika (Frontiers in Endocrinology, 2021)
FDA approved anti-obesity medications may not be cost effective for patients struggling with pre-operative weight loss prior to bariatric surgery. Metformin, a biguanide, and Topiramate , a carbonic anhydrase inhibitor, both cost effective medications, have demonstrated weight loss when used for the treatment of type 2 diabetes or seizures, respectively. The aim of the three cases is to demonstrate the clinical utility of topiramate and metformin for preoperative weight loss in patients with a body mass index (BMI) ≥ 50 kg/m2 prior to bariatric surgery who are unable to follow the bariatric nutritional prescription due to a dysregulated appetite system Each patient was prescribed metformin and/or topiramate in an off-label manner in conjunction with lifestyle modifications and achieved >8% total body weight loss during the preoperative period.